2014
DOI: 10.1111/1755-5922.12092
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Disease Risks of Nonthyroidal Illness Syndrome and Inflammatory Responses on Patients with Chronic Kidney Disease: From the Association to Clinical Prognosis

Abstract: SUMMARYBackground: Previous data have suggested the potential risk of low serum-free triiodothyronine (FT3) on the cardiovascular disease (CVD) events in patients with endstage renal disease (ESRD). However, the roles of FT3 and interleukin-6 (IL-6) in the developing of CVD events in patients with chronic kidney disease (CKD) have not been investigated. Patients and Methods: A total of 176 consecutive patients with CKD underwent thyroid function, IL-6, and echocardiography evaluation. They were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…and the decrease in T3 level was associated with worsening in prognosis [19], [20]. In a study performed in China in 2014 with patients diagnosed with chronic renal failure, it was found that the risk of mortality increased due to cardiovascular events in patients with NTIS (low T3, high IL-6 levels) [21]. When the findings of our study are examined, it could be seen that the increase in fT4 levels and the decrease in fT3 levels have a significant relationship with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…and the decrease in T3 level was associated with worsening in prognosis [19], [20]. In a study performed in China in 2014 with patients diagnosed with chronic renal failure, it was found that the risk of mortality increased due to cardiovascular events in patients with NTIS (low T3, high IL-6 levels) [21]. When the findings of our study are examined, it could be seen that the increase in fT4 levels and the decrease in fT3 levels have a significant relationship with mortality.…”
Section: Discussionmentioning
confidence: 99%